History of some diseases and pests in Eastern Gojjam from 1941 to 1991: History of diseases - Ayaleneh, Shimeles Lewoye (Ethiopian Journal of Social Sciences, 2024)
Eastern Gojjam is historically known as â€˜Gojjam Proper’ consisting of the three awuraja administrations of Debre Markos, Bichena, and Motta of Gojjam Governorate General or the later Gojjam Provincial Administration from 1941-1991. Eastern Gojjam is a potential agricultural area that has long suffered from diseases and pests. These two problems were the dominant factors that challenged the productivity of the region. Considering the frequency of diseases and pests in eastern Gojjam from 1941 to 1991, I investigated diseases and pests in eastern Gojjam from 1941 to 1991 to determine the responses of the government and to examine the major problems in the prevention and control of diseases and pests. In this study, I consulted archival materials at Debre Markos University about diseases such as Tesibo, cholera, malaria, and small-pox. Moreover, I studied the spread and preventive measures against pests like locusts and temch which frequently affected the people of East Gojjam from 1941 to 1991. The government tried to use its full capacity to utilize the available resources. Providing mobile medical services following the outbreak of diseases and pests was the main preventive and control mechanism. Shortage of skilled manpower, insufficient and poor health infrastructure, poor logistics and supplies, old tradition and wrong perceptions, and transportation and communication problems were among the major problems that challenged the prevention of diseases. On the other hand, the local people employed their traditional coping mechanisms in the prevention of diseases and pests in the absence of modern medical services